STAT2 Signaling Regulates Macrophage Phenotype During Influenza and Bacterial Super-Infection - Gopal, Radha; Lee, Benjamin; McHugh, Kevin J.; Rich, Helen E.; Ramanan, Krishnaveni; Mandalapu, Sivanarayana; Clay, Michelle E.; Seger, Philip J.; Enelow, Richard I.; Manni, Michelle L.; Robinson, Keven M.; Rangel-Moreno, Javier; et al. (Frontiers in Immunology, 2018)
Influenza is a common respiratory virus that infects between 5-20% of the US population and results in 30,000 deaths annually. A primary cause of influenza-associated death is secondary bacterial pneumonia. We have previously shown that influenza induces type I interferon (IFN)-mediated inhibition of Type 17 immune responses, resulting in exacerbation of bacterial burden during influenza and Staphylococcus aureus super-infection. In this study, we investigated the role of STAT2 signaling during influenza and influenza-bacterial super-infection in mice. Influenza-infected STAT2-/- mice had increased morbidity, viral burden, and inflammation when compared to wild-type mice. Despite an exaggerated inflammatory response to influenza infection, we found increased bacterial control and survival in STAT2 deficient mice during influenza-MRSA super-infection compared to controls. Further, we found that increased bacterial clearance during influenza-MRSA super-infection is not due to rescue of Type 17 immunity. Absence of STAT2 was associated with increased accumulation of M1, M2 and M1/M2 co-expressing macrophages during influenza-bacterial super-infection. Neutralization of IFNγ (M1) and/or Arginase 1 (M2) impaired bacterial clearance in Stat2-/- mice during super-infection, demonstrating that pulmonary macrophages expressing a mixed M1/M2 phenotype promote bacterial control during influenza-bacterial super-infection. Together, these results suggest that the STAT2 signaling is involved in suppressing macrophage activation and bacterial control during influenza-bacterial super-infection. Further, these studies reveal novel mechanistic insight into the roles of macrophage subpopulations in pulmonary host defense.